First Use of Superpulsed Fibre Thulium Laser-Based Contact Stone Ablation in Common Bile and Main Pancreatic Ducts - S. A. Budzinskiy; S. G. Shapovalyants; E. D. Fedorov; E. A. Vorobyeva; M. Yu. Svirin; M. G. Malyarov; P. L. Chernyakevich; E. N. Platonova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. A clinical demonstration of the feasibility of novel superpulsed thulium fibre laser in contact intraductal lithotripsy in patients with choledocholithiasis and pancreatic lithiasis.Key points. We describe two clinically successful ablations of large biliary and pancreatic calculi using a FiberLase U2 superpulse fibre thulium laser appliance (IRE-Polus, Russia) during oral transpapillary cholangiopancreaticoscopy in patients with technically unfeasible conventional minimally invasive treatment for choledocho- and pancreatic lithiasis. A 72-yo patient was urgently admitted with acute mechanical jaundice, cholangitis and a history of endoscopic papillosphincterotomy (EPST) and bilioduodenal stenting with a plastic implant for technically impractical lithotripsy and lithoextraction. An ineffective extracorporeal lithotripsy attempt was followed on day 3 by a second retrograde intervention and endoscopic contact laser lithotripsy controlled in oral transpapillary cholangioscopy with FiberLase U2. A 50-yo patient was admitted with clinical signs of chronic calculous pancreatitis and a history of EPST, pancreatic ductotomy and plastic pancreatic stenting. The first endoscopy stage comprised the encrusted pancreatic stent removal, retrograde pancreaticography, pancreatic ductotomy, narrowed terminal Wirsung’s duct bougienage with mechanical dilators and additional balloon-assisted dilation of the excision area and pancreatic stricture. Mechanical intraductal lithotripsy was unsuccessful. Contact lithotripsy with a novel superpulsed fibre thulium laser has been rendered. The technique presented ensures a complete sanation of the duct at no mucosal damage.Conclusion. We present the fully successful first national and world experience of the superpulsed fibre thulium laser application in contact lithotripsy of large calculi in common bile and main pancreatic ducts.